YbPd2In: A promising candidate for strong entropy accumulation at very low temperature - Gastaldo, F. (2019)
Fil: Sereni, J.G. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina; Universidad Nacional de Cuyo; Argentina